Modifications of binder for road surface dressing / Syarifah Anom Ibrahim - Ibrahim, Syarifah Anom (2005)
Higher traffic density and heavier axle load in Malaysia have increased tremendously in time with the country’s economic growth. This phenomenon has contributed problems to the road pavement. As far as the traffic factor is concerned, increased in traffic loads have contributed to the premature failure of pavement that is associated with overloading stresses. Surface cracking, rutting and stripping now becoming very serious problems. Previous studies have shown that by using conventional bitumen (unmodified bitumen) only as a binder cannot overcome such problems. Therefore, rubber or polymers as a modifier is now widely adopted in Europe and other developed countries. Surface dressing is quite commonly used for road rehabilitation as it provides low cost and the process of application is quite simple and straight forward. In this research, 40-mesh tyre crumbs and two types of polymers (Styrene-Butadiene-Styrene and Ethylene-Vinyl-Acetate) were used as additives to investigate their physical properties with respect to differences between unmodified bitumen and rubber-polymer blends modified binder. The percentage of rubber and polymers content varies from 1% up to 5% by weight of bitumen. In order to examine the basic physical characteristics of the modified binder, three tests were carried out, viz; penetration test, softening point test and dynamic shear rheometer test. The aging process was carried-out in the laboratory using rolling thin film oven test (RTFOT). Vialit and lap shear tests were carried-out to evaluate the bonding characteristics of the binders. The findings from this research work had shown that the addition of rubber- polymer into bitumen had increased the quality of the binder. The addition of rubber - polymer had significantly increased the viscosity and elastic properties of the binder, reduction of its temperature susceptibility and increased the bonding strength. Binder modification with rubber- polymer had shown better results when compared to modified binder with rubber only (no polymer). Almost similar findings in term of performance when compared with modification of binder with polymer only. In addition, modified binder with rubber-polymer would reduce the effect of aging and the results had shown a significant effect at high polymer concentration. In conclusion, this study had shown that for both physical and bonding tests, polymer SBS produces better results as compared to polymer EVA. With added polymer ranges from 1% to 5%, it was found that the optimum binder content for polymer EVA was 4% tyre crumbs - 4% polymer EVA, while as modified binder with SBS, the optimum mix composition was 5% tyre crumbs - 5% polymer SBS.